Just for new governors. - Bunce, Liam; Parker, David (Producer) (Academic Video Online, 2006)
When you're a new governor, how do you find out what governors actually do? 3 new governors are set challenges by Governance expert Judy Burgess designed to help them find out the role of a governing body. In this programme our governors discover how to set aims and visions, monitor and evaluate performance and find out who they are accountable to.